И небеса пронзит комета - Рой Олег (Мистика судьбы, 2015)
Экземпляры: ф.17 (20150921) / Инвентарный номер: 47206 / Цена: 225.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6